State sovereignty: political and legal interpretations - R V Mamedov (RUDN Journal of Law, 2011)
The article is devoted to the modern concepts of state sovereignty in the context of globalization and system crisis of human civilization which shows itself in the transformation of territorial concept of state as well as in the menaces to the state itself.